Preoperative Radiosurgery for Soft Tissue Sarcoma. (January 2018) - Kubicek, Gregory J.; LaCouture, Tamara; Kaden, Maureen; Kim, Tae Won; Lerman, Nati; Khrizman, Polina; Patel, Ashish; Xu, Qianyi; Lackman, Richard
Abstract : Objectives: Preoperative radiation followed by surgical resection is a standard treatment for soft tissue sarcomas (STSs). The conventional method of radiation is 5 weeks to approximately 50 Gy. We report on our initial experience and phase II single-arm study assessing 5 fractions of stereotactic body radiotherapy (SBRT), followed by surgical resection for STS. Methods: Thirteen patients and 14 tumors were treated with preoperative SBRT; tumors were mostly poorly differentiated (5) or myxoid (5) and were located on the leg (10), arm (2) or groin (2). The median tumor size in greatest dimension was 7.6 cm (maximum 16 cm). Twelve patients received 35 Gy in 5 fractions; for 2 deeper tumors the dose was 40 Gy in 5 fractions. Ten patients were administered 0.5 cm bolus to improve the dose. Gross tumor volume was expanded 0.5 cm radially and 3 cm along the tissue plane. Treatment was to an isodose line (median 81%) and was delivered every other day. Maximum dose to the skin was 46 Gy (median 41 Gy). Results: The median follow-up period was 279 days. Surgical resection occurred a median of 37 days after completion of SBRT. Four patients had acute toxicity consisting of 2 grade 2 and 2 grade 3 skin reactions; all cases of skin toxicity resolved by the time of surgery. Percent tumor necrosis ranged from 10% to 95% (median 60%). All patients had negative margins. Planned vacuum-assisted wound closure was used in 4 patients; there were no other major wound complications. There was 1 local recurrence and 7 distant recurrences. Conclusion: This is the initial experience of radiosurgery for preoperative treatment of STSs. We have found this to be well tolerated, convenient for the patients, and a much shorter treatment course, allowing patients to undergo surgery and subsequent chemotherapy quicker. Surgical complications and control rates are satisfactory. The initial results are encouraging for further investigation.